Clinical Significance of Mucinous Rectal Adenocarcinoma following Preoperative Chemoradiotherapy and Curative Surgery. Issue 1 (January 2016) - Kim, Tae Gyu; Park, Won; Choi, Doo Ho; Park, Hee Chul; Kim, Seok-Hyung; Cho, Yong Beom; Yun, Seong Hyeon; Kim, Hee Cheol; Lee, Woo Yong; Lee, Jeeyun; Park, Joon Oh; Park, Young Suk; et al.
Aims: To investigate the efficacy and prognosis associated with preoperative chemoradiotherapy in patients with locally advanced mucinous rectal cancer (MRC). Methods: Our analysis included 412 patients who underwent preoperative chemoradiotherapy and curative surgery for locally advanced rectal cancer. Among these patients, 30 had MRC and 382 had nonmucinous rectal cancer (NMRC). Tumor downstaging, defined as a lower pathologic stage than clinical stage, and survival were compared between MRC and NMRC. Results: Increased frequency of cT4 disease was seen in MRC compared to NMRC (23.3% vs 8.9%, p = 0.021). Complete pathologic response rate and tumor downstaging rate were 0% and 23.3% in MRC and 15.4% and 52.4% in NMRC, respectively (p = 0.025 and p = 0.002). There was no significant difference in disease-free survival between the 2 groups (62.1% vs 75.0% at 5 years, p = 0.170), while there was a significantly lower overall survival in MRC vs NMRC (67.4% vs 88.0% at 5 years, respectively; p = 0.012). When analyzed by stage, the overall survival difference between MRC and NMRC was significant in the cT3 group (71.1% vs 89.1% at 5 years, p = 0.047) and marginally significant in the cT4 group (51.4% vs 74.5% at 5 years, p = 0.053), but not significant in subgroups with the same pathologic stage. Conclusions: Mucinous rectal cancer is related to a lower response rate to chemoradiotherapy and poorer prognosis compared to NMRC, even when corrected for clinical stage. The poor prognosis in MRC might be associated with poor responsiveness to preoperative chemoradiotherapy.